The Modern Planning History of East Asia: a brief guide from the Japanese perspectives - Watanabe, Shun-ichi (International Planning History Society Proceedings, 2018)
Three years from now in 2019, we will celebrate the 100th year of Japan’s City Planning Act (“Old Act,” 1919). The Old Act was the Japanese positive response to western modern planning, which was developed in western Europe and north America in the late 19th and early 20th centuries and was gradually spreading all over the world. Japan was the first nation in East Asia which systematically responded to this spreading process (Watanabe 1993) and, after establishing the Old Act system in the Japanese homeland, spread it in turn to the neighboring countries and regions in the process of imperial expansion. This “dual spread” is a very interesting topic particularly to comparative planning researchers. In this presentation, we plan to draw a rough sketch of the spreading process of western modern planning in East Asia from the viewpoint of Japan, as it was a crucially important spreading channel from the west. There were, however, another such channels to East Asia, especially to China. As planning history studies are now growing in China, we have to keep our eyes open to them if we are going to have a comprehensive planning history of East Asia. With this limitation in mind, we present some crucial research points and highlights in order to raise interests in East Asian planning history, particularly for external researchers. Therefore, we have tried to develop many stimulating research questions, hoping to see the IPHS become a forum of international exchanges in a really productive manner.